Contributions from carbon and nitrogen in roots to closing the yield gap between conventional and organic cropping systems - Córdoba, Eva María; Chirinda, Ngonidzashe; Li, F.; Olesen, Jørgen E. (Wiley, 2018)
This study investigates the effect of different crop rotation systems on carbon (C) and nitrogen (N) in root biomass as well as on soil organic carbon (SOC). Soils under spring barley and spring barley/pea mixture were sampled both in organic and conventional crop rotations. The amounts of root biomass and SOC in fine (250–253 μm), medium (425–250 μm) and coarse (>425 μm) soil particulate organic matter (POM) were determined. Grain dry matter (DM) and the amount of N in harvested grain were also quantified. Organic systems with varying use of manure and catch crops had lower spring barley grain DM yield compared to those in conventional systems, whereas barley/pea showed no differences. The largest benefits were observed for grain N yields and grain DM yields for spring barley, where grain N yield was positively correlated with root N. The inclusion of catch crops in organic rotations resulted in higher root N and SOC (g C/m2) in fine POM in soils under barley/pea. Our results suggest that manure application and inclusion of catch crops improve crop N supply and reduce the yield gap between conventional and organic rotations. The observed positive correlation between root N and grain N imply that management practices aimed at increasing grain N could also increase root N and thus enhance N supply for subsequent crops.